2021
DOI: 10.1590/1414-431x2021e10867
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 induces apoptosis via p38 MAPK in human lung cancer cells

Abstract: Lung cancer is one of the most common cancers worldwide. TRPV4 belongs to the 'transient receptor potential' (TRP) superfamily. It has been identified to profoundly affect a variety of physiological processes, including nociception, heat sensation, and inflammation. Unlike other TRP superfamily channels, its roles in cancers are unknown. Here, we elucidated the effects of TRPV4 and molecular mechanisms in human lung cancer cells. The levels of TRPV4 were detected in human lung cancer tissues and the paired par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…59 It has been widely reported that many key genes affecting lung cancer function through these two pathways. 60,61 In this study, changes in HBA and HBB affected the synthesis of p38 and JNK proteins, suggesting that they may also have a similar mechanism of action. which is a new starting point on searching for biomarkers.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…59 It has been widely reported that many key genes affecting lung cancer function through these two pathways. 60,61 In this study, changes in HBA and HBB affected the synthesis of p38 and JNK proteins, suggesting that they may also have a similar mechanism of action. which is a new starting point on searching for biomarkers.…”
Section: Discussionsupporting
confidence: 51%
“…JNK signaling pathway regulates lamellipodium formation and cell mobility, and plays a critical role in lung cancer invasiveness and metastasis 59 . It has been widely reported that many key genes affecting lung cancer function through these two pathways 60,61 . In this study, changes in HBA and HBB affected the synthesis of p38 and JNK proteins, suggesting that they may also have a similar mechanism of action.…”
Section: Discussionmentioning
confidence: 56%
“…Overexpression of TRPV4 in lung cancer cells promotes apoptosis by stimulating the p38 MAPK pathways [71]. In squamous cell carcinoma (SSC), oxidative stress induced apoptosis within 24 h of H 2 O 2 application.…”
Section: Apoptosis Induced By Modulation Of the Redox Trp Channelsmentioning
confidence: 99%
“…The inhibition of p38 MAPK reduces TRPV4's effects on the cell proliferation, apoptosis, and migration of those cells. Collectively, this can imply that TRPV4 is a candidate target for human lung cancer therapy [239].…”
Section: Trpv4mentioning
confidence: 99%